2018
DOI: 10.3390/ijgi8010011
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in Using Indoor Maps for Wayfinding in Real Environments

Abstract: Users more easily become lost in complex indoor environments than in outdoor environments. Users with diverse backgrounds encounter different self-location, route memorization, and route following problems during wayfinding. This study intends to explore gender and age effects on the use of indoor maps for wayfinding in real environments. We used eye-tracking and retrospective verbal protocol methods to conduct a wayfinding experiment in a newly opened building. Statistical data were collected and three findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Lin [13] designed wayfinding tasks in a virtual environment and did not find conclusive evidence supporting the hypothesis that males perform better than females. Wang [14] also found no significant differences between males and females. Hegarty [15] found that males and females do not show differences in accuracy and reaction time.…”
Section: Sexed-related Research In Wayfindingmentioning
confidence: 89%
“…Lin [13] designed wayfinding tasks in a virtual environment and did not find conclusive evidence supporting the hypothesis that males perform better than females. Wang [14] also found no significant differences between males and females. Hegarty [15] found that males and females do not show differences in accuracy and reaction time.…”
Section: Sexed-related Research In Wayfindingmentioning
confidence: 89%
“…Mummidi and Krumm [20] calculated salience by comparing the number of times a specific n-gram appears in a cluster (term frequency) with the number of times the same n-gram appears in all clusters combined (document frequency). Wang [21] combined expert knowledge and proposed some definitions from cognitive and computational perspectives to evaluate indoor landmark salience. However, such methods are cumbersome and labor intensive.…”
Section: Indoor Landmark Salience Modelsmentioning
confidence: 99%
“…Participants displayed a significant tendency to choose the path leg offering the longest line of sight during free exploration, but that trend did not occur in the chosen route group. Wang [21] reported that although males and females had similar levels of effectiveness and efficiency in self-location, route memorization, and route following, there was a significant difference between them in map reading and indoor wayfinding tasks. However, little research has measured the differences in landmark salience between the self-location and orientation tasks in indoor environments.…”
Section: Differences In Landmark Salience During Wayfindingmentioning
confidence: 99%
See 1 more Smart Citation
“…C. Wang et al [17] reflect "Gender and Age Differences in Using Indoor Maps for Wayfinding in Real Environments". This study intends to explore gender and age effects on the use of indoor maps for wayfinding in real environments.…”
Section: Hci and Gis In This Issuementioning
confidence: 99%